Utilization of Kitchen Waste as a Learning Media in Increasing Children's Creativity - Nur Aisyah; Fathor Rozi; Holila Holila; Anis Sulalah Trianingsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Waste that is appropriately managed will produce creativity that can make. Waste is also able to develop children's intelligence with proper utilization. This study aims to examine the use of kitchen waste as a medium in increasing students' creativity. The place of research was conducted at an early childhood education institution located in the Probolinggo area, namely the Salih Children's Education Park; this institution is under the auspices of the Nurul Jadid Paiton Foundation Probolinggo. The research method uses a qualitative approach type of case study to get an idea of increasing students' creativity by utilizing kitchen waste media. Informant sources were obtained from school principals, ustadzah-ustadzah and Taman Pendidikan Anak Salih students. The results showed; That every weekend, namely Saturday, the Anak ShalihEducation Park institution conducts routine cooking class activities carried out at school; this activity produces kitchen waste; in anticipation that waste does not become a negative thing and remains functional, the Ustadzah of Anak ShalihEducation Park innovates to manage kitchen waste media to be used as creativity material for students. The use of kitchen waste as a learning medium is carried out by; Preparatory analysis, applying waste media, and creativity assessment. By using cooking class kitchen waste as a learning medium, students are more enthusiastic, creative, exploratory, innovative and able to find new ideas by using various media to produce different kinds of artwork.